EFFECTS OF STAD COOPERATIVE LEARNING STRATEGY ON THE ACADEMIC ACHIEVEMENT OF SENIOR SECONDARY SCHOOL STUDENTS IN BIOLOGY IN BAUCHI METROPOLIS - Jacob Ndahi Ibrahim; Akarinwan Christopher; Okolo Nkemchor Mercy (Galaxy International Interdisciplinary Research Journal, 2022)
This study investigated on the Effects of STAD Cooperative Learning Strategy on the Academic Achievement of Senior Secondary School Students in Biology in Bauchi Metropolis. A post-test-control group design quasi experimental design was adopted. A sample of 83 students participated in the study were selected randomly from two schools in Bauchi Metropolis. An essay, Biology Achievement Test (BAT) used as an instrument for data collection. The instrument was analyzed using mean, standard deviation and independent sampled-test. The reliability of the instrument obtained using Pearson Product Correlation was 0. 842. Two hypotheses was formulated and tested at 0.05 level of significances. The study found that there was a significant difference in the mean achievement scores between Students taught Biology using STAD Cooperative Learning strategy and those taught with lecture method. Moreover, the study shows that there was no significant difference between the mean achievement scores of male and female students taught with STAD cooperative learning. The study recommends that government should encourage secondary schools’ teachers to adopt STAD cooperative strategy as an instructional approach for teaching Biology in secondary Schools to improve students’ achievement.